Investigating membrane selectivity based on polymer swelling - Farid, Osama (2011)
Nanofiltration has many potential applications as a separation technology for processes that use mixtures of aqueous and organic solvents, for example alcohol/water mixtures. Membrane systems are well established for separations carried out in aqueous media, however they have seen a much slower rate of uptake in non-aqueous processes or with aqueous/organic mixtures. This is because the interaction between membrane and solvent(s) dictates both the permeability and selectivity, and there is currently limited criterion for identifying the theoretical performance of a membrane based on the properties of a bulk polymeric material. The small numbers of commercial successes to date have arisen from empirical findings, with no agreed methodology by which new candidate membrane materials can be identified.